The essence of the New Testament : a survey - Towns, Elmer L.; Gutierrez, Ben. (Nashville, Tenn. : B & H Academic, 2012)
The Essence of the New Testament surveys the books from Matthew to Revelation. Based on decades of scholarly research and classroom teaching, a team of biblical scholars from Liberty University provides a practical, readable, and insightful introduction to the second major division of the Christian biblical canon. This uniquely illustrated, full-color volume features book introductions, background studies, outlines, surveys, theological concepts, practical applications, study questions, and helpful word studies. Editors Elmer Towns and Ben Gutierrez draw from their lives as teachers to provide a well tested and proven New Testament overview written at the collegiate level, yet appropriate for pastors, scholars, and laymen alike. They represent the finest evangelical scholarship along with a passion to open windows of spiritual and practical insight into the biblical text. This exciting new survey of the Scriptures highlights the key elements of the New Testament. The history, archaeology, and wisdom of the biblical world are revealed with an eye on the application of their moral principles, theological insights, and practical application to today's world.
How We Cot the New Testament -- Interpreting the New Testament -- The History Between the Testaments -- The Essence of the Synoptic Problem -- Matthew: The Kingdom of Heaven -- Mark: The Divine Servant -- Luke: The Son of Man -- John: Believe and Live -- Acts: Taking the Message to the World -- Romans: Righteousness by Faith -- 1 Corinthians: The Supremacy of Love -- 2 Corinthians: Power in Weakness -- Galatians: By Grace through Faith -- Ephesians: Wealth, Walk, and Warfare -- Philippians: The Mind of Christ -- Colossians: Preeminence of Christ -- 1 Thessalonians: The Return of Christ -- 2 Thessalonians: The Day of the Lord 19 -- 1 Timothy: Pastoral Principles -- 2 Timothy: Final Words -- Titus: Good Works -- Philemon: Social Dynamics of the Gospel -- Hebrews: Jesus Our Great High Priest -- James: Faith That Works -- 1 Peter: Holy Living -- 2 Peter: Growing in Grace -- 1 John: Blessed Assurance -- 2 John: Avoid False Teachers -- 3 John: Accept True Teachers -- Jude: Final Warnings -- Revelation: The King Is Coming.
Includes bibliographical references and indexes.
Keywords: Bible. -- Introductions; Bible. -- Criticism, interpretation, etc; Bible. O.T. -- study; Bible. N.T. -- history of biblical events